2018
DOI: 10.1155/2018/1743253
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative‐Nitrative Stress and Poly (ADP‐Ribose) Polymerase Activation 3 Years after Pregnancy

Abstract: Background Oxidative-nitrative stress and poly (ADP-ribose) polymerase activation have been previously observed in healthy and gestational diabetic pregnancies, and they were also linked to the development of metabolic diseases. The aim of the present study was to examine these parameters and their correlation to known metabolic risk factors following healthy and gestational diabetic pregnancies. Methods Fasting and 2 h postload plasma total peroxide level, protein tyrosine nitration, and poly (ADP-ribose) pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We hypothesize that this lower LDH reflects the decreased trophoblast invasion. Additionally, it has been previously shown by our research group that even after a healthy pregnancy, the degree of oxidative stress is elevated after three years [16]. It is also conceivable that low-resistance pregnant women had higher oxidative stress levels because of their higher number of previous pregnancies.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…We hypothesize that this lower LDH reflects the decreased trophoblast invasion. Additionally, it has been previously shown by our research group that even after a healthy pregnancy, the degree of oxidative stress is elevated after three years [16]. It is also conceivable that low-resistance pregnant women had higher oxidative stress levels because of their higher number of previous pregnancies.…”
Section: Discussionmentioning
confidence: 69%
“…According to this reaction pathway, the change in nitrotyrosine levels might be expected to follow the changes in PRX concentration. On the other hand, previous studies also failed to confirm to this relationship, especially in chronic disease and healthy conditions [16,25].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, increased circulating levels of biomarkers of oxidative stress were shown to associate with multiple agerelated diseases, including cancer, diabetes mellitus [21], neurodegenerative diseases, and cardiovascular diseases, as Oxidative Medicine and Cellular Longevity well as pathological conditions characterized by ongoing inflammatory processes [37,38]. On another note, nitrative stress-imposed by reactive derivatives of NO-contributes to a plethora of pathophysiological processes as well as aging [7,[39][40][41]. This study also found that concentrations of urinary biomarkers of oxidative stress varied considerably in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Under nitrosative stress, ONOO – not only induces DNA single-strand breaks but also activates PARP ( Buelow et al, 2009 ), which consumes a large amount of NAD + , resulting in energy depletion and necrotic cell death. One study showed that DNA nitration is upstream of PARP-1 activation ( Barany et al, 2017 ; Horvath et al, 2018 ). The initial signaling of PARP-1 in mitochondria is mediated by the downstream activation of JNK-1, a stress-activated protein kinase (SAPK).…”
Section: Mechanisms Of the Cell Death Caused By Nitrosative Stressmentioning
confidence: 99%